Development of 'CrossChemistry Games': A web-based educational game on organic chemistry topics - Luthfia Ulva Irmita; Aqueenfa Zevanna; Joan Theresia Limas; Made Dayanand Premachandra Pribadi (Privietlab, 2025)
This research aims to develop the CrossChemistry Games educational game as a learning medium for Organic Chemistry material and to determine the feasibility and response of students to the CrossChemistry Games. This type of research is Research and Development (R&D) research using the ADDIE development model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. In this study, only the Analysis, Design, and Development stages were carried out. The subjects of this research were 36 students in grade 11 at Wardaya High School. The feasibility test of learning media refers to the validation results of media and material experts. The research results showed that the results of the validation test for the CrossChemistry Games learning media met the valid criteria with a validity value of 82%, and students' responses to the CrossChemistry Games learning media met the very good criteria with a value of 87%. This research has important implications for increasing the use of learning media in chemistry learning at Wardaya High School. The use of learning media combined with technology will support education in the 5.0 era and can increase student involvement, facilitate understanding of chemical concepts, and improve thinking and problem-solving skills. It is recommended that technology-based learning media be integrated into broader chemistry learning strategies.